1991
DOI: 10.1093/cvr/25.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous plasma Na,K-ATPase inhibitory activity and digoxin like immunoreactivity after acute myocardial infarction

Abstract: The results show that plasma factor(s) with some of the properties of digitalis are increased in acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…Hamlyn et al (1) demonstrated that there is a substance in plasma that cannot yet be distinguished from ouabain, even by electrospray ionization-mass spectrometry, 1 H-NMR, and liquid chromatography (2)(3)(4). Furthermore, the observation that this endogenous ouabain and its analogs increase during exercise (5), salty meals (6), and pathological conditions [such as arterial hypertension, eclampsia (7), and myocardial infarction (8)] raised the possibility that it may function as a hormone (9). This theory prompted efforts to unravel its physiological role (10).…”
mentioning
confidence: 99%
“…Hamlyn et al (1) demonstrated that there is a substance in plasma that cannot yet be distinguished from ouabain, even by electrospray ionization-mass spectrometry, 1 H-NMR, and liquid chromatography (2)(3)(4). Furthermore, the observation that this endogenous ouabain and its analogs increase during exercise (5), salty meals (6), and pathological conditions [such as arterial hypertension, eclampsia (7), and myocardial infarction (8)] raised the possibility that it may function as a hormone (9). This theory prompted efforts to unravel its physiological role (10).…”
mentioning
confidence: 99%
“…Although several studies have shown a correlation between elevated endogenous cardiac glycosides and certain pathological conditions, the physiological function of endogenous cardiac glycoside-like compounds is still uncertain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17). In addition, marked increases in endogenous ouabain-like compounds occur in congestive heart failure, both in animal models and human patients (18)(19)(20). One concern raised with respect to endogenous cardiac glycoside-like compounds is that they occur in levels which may not significantly inhibit the Na,K-ATPase.…”
mentioning
confidence: 99%
“…The identification of cardiac glycoside-like molecules in mammals has led to the proposal that these compounds are natural regulators of Na,K-ATPase in vivo (7)(8)(9)(10). Several studies have shown a correlation between these cardiac glycoside-like molecules and certain pathological conditions, such as hypertension and heart failure (11)(12)(13)(14)(15)(16)(17). Plasma levels of these putative ligands for the Na,KATPase are high in several animal hypertension models, as well as in human essential hypertension and preeclampsia (11-14, 18, 19).…”
mentioning
confidence: 99%
“…Plasma levels of these putative ligands for the Na,KATPase are high in several animal hypertension models, as well as in human essential hypertension and preeclampsia (11-14, 18, 19). In addition, marked increases in peripheral and central endogenous ouabain-like compounds occur in animal models of congestive heart failure as well as in human patients (15)(16)(17). However, it is still difficult to draw definitive conclusions regarding the specific function of these molecules in pathophysiology.…”
mentioning
confidence: 99%